2021
DOI: 10.1136/jitc-2020-001818
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplantation cyclophosphamide reduces the incidence of acute graft-versus-host disease in patients with acute myeloid leukemia/myelodysplastic syndromes who receive immune checkpoint inhibitors after allogeneic hematopoietic stem cell transplantation

Abstract: BackgroundImmune checkpoint inhibitors (ICIs) are being used after allogeneic hematopoietic stem cell transplantation (alloHCT) to reverse immune dysfunction. However, a major concern for the use of ICIs after alloHCT is the increased risk of graft-versus-host disease (GVHD). We analyzed the association between GVHD prophylaxis and frequency of GVHD in patients who had received ICI therapy after alloHCT.MethodsA retrospective study was performed in 21 patients with acute myeloid leukemia (n=16) or myelodysplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“… 46,47 In 1 institution, cyclophosphamide after SCT permitted the initiation of ICI therapy much earlier in the course of the relapse. 52 …”
Section: Hematologic Toxicity Of Ici Treatment Of Hematologic Maligna...mentioning
confidence: 99%
“… 46,47 In 1 institution, cyclophosphamide after SCT permitted the initiation of ICI therapy much earlier in the course of the relapse. 52 …”
Section: Hematologic Toxicity Of Ici Treatment Of Hematologic Maligna...mentioning
confidence: 99%
“…Therefore, we suggest that early initiation of ICIs therapy after allo-HSCT is feasible and deserves attention. Besides, a recent study has also showed that irAEs directly attributed to ICIs therapy may be alleviated in patients with AML/myelodysplastic syndrome (MDS) who receive post-transplantation cyclophosphamide as GVHD prophylaxis ( 45 ). Currently, we have not changed our conditioning regimen in advance considering the possibility of disease relapse and ICIs therapy.…”
Section: Discussionmentioning
confidence: 99%
“…33 In the posttransplant setting, another analysis of 21 patients with AML and MDS treated with ICIs following allo-SCT relapse demonstrated that the use of PTCy prophylaxis was associated with a 90% reduced risk of acute GVHD. 34 CD47/SIRPΑ BLOCKADE CD47 is a widely expressed transmembrane protein that interacts with the signal regulatory protein α (SIRPα) expressed on the surface of macrophages and dendritic cells. 35 This interaction between CD47 and SIRPα leads to downstream signaling and inhibition of phagocytosis.…”
Section: Safety Of Icis In the Peritransplant Settingmentioning
confidence: 99%